Gliadin encapsulated PCOs nanoformulation: An effective therapeutic option for metastatic breast cancer - Sant Lal; Monika Kataria; Neeraj Dilbaghi (Hybrid Advances)
Breast carcinoma ranks as one of the most dominant cause of mortality among women worldwide, with metastatic breast cancer posing a significant therapeutic challenge due to its high fatality rate and propensity to spread to critical organs like the lungs and brain. Despite their effectiveness, current cancer treatments frequently have serious side effects, which emphasizes the need for safer and more efficient therapeutic alternatives. Procyanidolic oligomers (PCOs), natural antioxidants derived from grape seeds, have shown promise as anticancer agents, particularly in diseases driven by oxidative stress. Building on this foundation, we hypothesized that nanoformulation of PCOs could enhance their therapeutic potential. In this study, we synthesized a stable nanoformulation of PCOs (termed PCOs–NF) using a modified desolvation method and characterized it through SEM and TEM analyses, revealing a consistent spherical morphology and an average diameter of 156 nm. The anticancer efficacy of PCOs–NF was evaluated against MCF-7 (human breast cancer), L-132 (human lung cancer), and HBL-52 (human brain meningioma) cell lines using the MTT assay. Results demonstrated significant inhibition of cell viability, with values of 36.46 %, 33.97 %, and 36.30 %, respectively, at a concentration of 125 μg/ml—exceeding the performance of conventional anticancer drugs. These findings highlight the potent anticancer activity of PCOs–NF against key cell lines involved in breast cancer metastasis to the lungs and brain. The study underscores the potential of PCOs–NF as a natural, selective, and efficient therapeutic option for metastatic breast cancer therapy. Further research and clinical validation could pave the way for its development as a safer alternative to conventional treatments for metastatic cancers.